Fetuin-A in Infants Born Small- or Large-for-Gestational-Age - Wang, Wen-Juan; Wang, Shufan; Yang, Meng-Nan; Dong, Yu; He, Hua; Fang, Fang; Huang, Rong; Yu, Xiao-Gang; Zhang, Guang-Hui; Zhao, Xia; Zheng, Tao; Huang, Xiao-Yi; et al. (Frontiers in Endocrinology, 2020)
Fetuin-A is a multifunctional glycoprotein that has been implicated in insulin resistance and bone metabolism. We assessed whether fetuin-A is associated with poor or excessive fetal growth. In the Shanghai Birth Cohort, we conducted a nested case-control study of 60 trios of small-for-gestational-age (SGA, birth weight <10th percentile), optimal-for-gestational-age (OGA, 25-75th, the reference) and large-for-gestational-age (LGA, >90th percentile) infants matched by sex and gestational age. Cord plasma concentrations of fetuin-A and fetal growth factors [insulin, proinsulin, insulin-like growth factor (IGF)-I and IGF-II] were measured. Cord plasma fetuin-A concentrations were higher in SGA (809.4±306.9 μg/ml, P=0.026) and LGA (924.2±375.9 μg/ml, P<0.001) relative to OGA (680.7±262.1 μg/ml) newborns, and were not correlated to insulin, proinsulin, IGF-I and IGF-II (all P>0.2). Higher fetuin-A concentrations were associated with increased risks of SGA [OR=1.67 (1.08-2.58) per SD increment, P=0.024] and LGA [OR=2.36 (1.53-3.66), P<0.001]. Adjusting for maternal and neonatal characteristics and fetal growth factors, the elevated risk changed little for LGA [adjusted OR=2.28 (1.29-4.01), P=0.005], but became non-significant for SGA (P=0.202). Our study is the first to demonstrate that fetuin-A may be involved in excessive fetal growth. This association is independent of fetal growth factors.